Cognitive Constraints on the Simple View of Reading: A Longitudinal Study in Children With Intellectual Disabilities. (4th July 2018) - van Wingerden, Evelien; Segers, Eliane; van Balkom, Hans; Verhoeven, Ludo
ABSTRACT: The present article aimed to explore how the development of reading comprehension is affected when its cognitive basis is compromised. The simple view of reading was adopted as the theoretical framework. The study followed 76 children with mild intellectual disabilities (average IQ = 60.38, age 121 months) across a period of 3 years. The children were assessed for level of reading comprehension (outcome variable) and its precursors decoding and listening comprehension, in addition to linguistic skills (foundational literacy skills, rapid naming, phonological short-term memory, verbal working memory, vocabulary, and grammar) and non-linguistic skills (nonverbal reasoning and temporal processing). Reading comprehension was predicted by decoding and listening comprehension but also by foundational literacy skills and nonverbal reasoning. It is concluded that intellectual disabilities can affect the development of reading comprehension indirectly via linguistic skills but also directly via nonlinguistic nonverbal reasoning ability.